Responding to Outbreaks of Human Immunodeficiency Virus Among Persons Who Inject Drugs—United States, 2016–2019: Perspectives on Recent Experience and Lessons Learned. (2nd September 2020) - Lyss, Sheryl B; Buchacz, Kate; McClung, R Paul; Asher, Alice; Oster, Alexandra M
Abstract: In 2015, a large human immunodeficiency virus (HIV) outbreak occurred among persons who inject drugs (PWID) in Indiana. During 2016–2019, additional outbreaks among PWID occurred across the United States. Based on information disseminated by responding health departments and Centers for Disease Control and Prevention (CDC) involvement, we offer perspectives about characteristics of and public health responses to 6 such outbreaks. Across outbreaks, injection of opioids (including fentanyl) or methamphetamine predominated; many PWID concurrently used opioids and methamphetamine or cocaine. Commonalities included homelessness or unstable housing, previous incarceration, and hepatitis C virus exposure. All outbreaks occurred in metropolitan areas, including some with substantial harm reduction and medical programs targeted to PWID. Health departments experienced challenges locating case patients and contacts, linking and retaining persons in care, building support to strengthen harm-reduction programs, and leveraging resources. Expanding the concept of vulnerability to HIV outbreaks and other lessons learned can be considered for preventing, detecting, and responding to future outbreaks among PWID.